Studi kelayakan bisnis: Studi pada blunotblu coffe sepeda kargo - Nasikhah, Mazroatun (Maliki Interdisciplinary Journal, 2025)
This business feasibility study examines the business potential of "Blunotblue Coffee," a private company that offers quality coffee services using cargo bikes in Malang City. Considering the high demand for coffee among workers and students, Blunotblue is here as a practical solution to meet coffee demand without sacrificing time and productivity. This study includes an in-depth analysis of legal, environmental, market, technical and management aspects, and shows the suitability of an environmentally friendly and efficient business model. The analysis results show that Blunotblue Coffee is feasible to operate, with large market potential and innovative marketing strategies. With a flexible and sustainable approach, Blunotblue is committed to providing a satisfying coffee experience while supporting a modern lifestyle.